HUBUNGAN TINGKAT PENGETAHUAN DAN SIKAP PETUGAS KESEHATAN DENGAN KEPATUHAN TERAPI ANTIRETROVIRAL (ARV) PADA ORANG DENGAN HIV/ AIDS DI PUSKESMAS TIKALA KOTA MANADO - Musfirah, Musfirah Ahmad; Adriani, Adriani Natalia; Sefty, Sefty Rompas; Dinda, Dinda Pasune (Bina Generasi : Jurnal Kesehatan, 2024)
Background: Human Immunodeficiency Virus (HIV) is a virus that damages the body's immune system by infecting and destroying CD4 cells so that it requires adherence in undergoing ARV therapy to maintain the patient's immune system. Aims: This study aims to identify the relationship between level of knowledge and adherence to antiretroviral therapy (ARV) in people with HIV/AIDS (PWHA) at the Tikala Community Health Center, Manado City. Methods: The research method used was cross sectional with a sample of 87 respondents who were selected using a purposive sampling technique. The ARV therapy adherence questionnaire uses a standard questionnaire, namely Morisky Medication Adherence Scale-8 (MMAS-8). Results: The results of this study indicate that most HIV/AIDS patients undergoing ARV therapy have a good level of knowledge where the attitude given by health workers can affect the level of comfort, trust, and satisfaction of PWHA during the treatment process which makes PWHA have good adherence to therapy. Conclusion: Support for health workers in serving PWHA which is very influential in building good relations between health workers and PWHA, especially in increasing adherence to undergoing ARV therapy to slow disease progression and improve quality of life.